Microbiota-dependent influence of prebiotics on the resilience of infant gut microbiota to amoxicillin/clavulanate perturbation in an in vitro colon model - Endika, Martha F.; Barnett, David J. M.; Klostermann, Cynthia E.; Schols, Henk A.; Arts, Ilja C. W.; Penders, John; Nauta, Arjen; Smidt, Hauke; Venema, Koen (Frontiers in Microbiology, 2023)
Antibiotic exposure disturbs the developing infant gut microbiota. The capacity of the gut microbiota to recover from this disturbance (resilience) depends on the type of antibiotic. In this study, infant gut microbiota was exposed to a combination of amoxicillin and clavulanate (amoxicillin/clavulanate) in the in vitro colon model (TIM-2) with faecal microbiota from 1-month-old (1-M; a mixed-taxa community type) as well as 3-months-old (3-M; Bifidobacterium dominated community type) breastfed infants. We investigated the effect of two common infant prebiotics, 2’-fucosyllactose (2’-FL) or galacto-oligosaccharides (GOS), on the resilience of infant gut microbiota to amoxicillin/clavulanate-induced changes in microbiota composition and activity. Amoxicillin/clavulanate treatment decreased alpha diversity and induced a temporary shift of microbiota to a community dominated by enterobacteria. Moreover, antibiotic treatment increased succinate and lactate in both 1- and 3-M colon model, while decreasing the production of short-chain (SCFA) and branched-chain fatty acids (BFCA). The prebiotic effect on the microbiota recovery depended on the fermenting capacity of antibiotic-exposed microbiota. In 1-M colon model, the supplementation of 2’-FL supported the recovery of microbiota and restored the production of propionate and butyrate. In 3-M colon model, the GOS supplementation supported the recovery of microbiota and increased the production of acetate and butyrate.